2018
DOI: 10.1002/ajpa.23711
|View full text |Cite
|
Sign up to set email alerts
|

Genetic history of Chad

Abstract: Objectives: The Sahel is a semi-arid zone stretching from the Atlantic Ocean in the west to the Red Sea in the east and from the Sahara in the north to the Sudanian Savanna in the south. Here, we investigated the genetic history of the spread of Northern African ancestry common among Berbers, the Y DNA haplogroup R1b-V88, and Chadic languages throughout the Sahel, with a focus on Chad. Materials and Methods: We integrated and analyzed genotype data from 751 individuals from Chad, Burkina Faso, Mali, South Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…2c ). Previous studies on trans-Sahelian migration to west Africa have suggested two distinct waves of migration: one more than 100 generations ago (2,900 years ago) and a more-recent wave in the last 35 generations (1,015 years ago) 24 . On the basis of a variety of east African proxy populations, we estimated that admixture in BRN occurred approximately 50 to 70 generations ago (1,500–2,000 years ago) (Fig.…”
Section: Insights Into Migration and Admixturementioning
confidence: 99%
“…2c ). Previous studies on trans-Sahelian migration to west Africa have suggested two distinct waves of migration: one more than 100 generations ago (2,900 years ago) and a more-recent wave in the last 35 generations (1,015 years ago) 24 . On the basis of a variety of east African proxy populations, we estimated that admixture in BRN occurred approximately 50 to 70 generations ago (1,500–2,000 years ago) (Fig.…”
Section: Insights Into Migration and Admixturementioning
confidence: 99%
“…It has been well established that in the populations of eastern and central Sahel there is a discernible Eurasian genetic component introduced over a long period of time by numerous migration events from different non‐African regions (Galego Llorente et al, ; Haber et al, ; Pickrell et al, ). Successive waves of migration are clearly reflected in both maternal and paternal genetic pools (Bučková et al, ; Černý et al, ; Podgorná et al, ; Shriner & Rotimi, ) and also in autosomal datasets as shown by allele frequency based methods (Triska et al, ; Vicente et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is present in many other populations, especially in Arabic speakers (Kulichová et al, ). It has been suggested that R1b‐V88 was introduced to this region by Arabic‐speaking pastoralists and represents the genetic signature of the Baggarization process and not the expansion of proto‐Chadic languages (Shriner & Rotimi, ). According to this scenario, R1b‐V88 has been gradually spreading through the Sahel from the 13th century onwards and was introduced into the gene pool of Chadic‐speaking populations (such as the Hausa and Mada) as recently as just 300 years ago (Shriner & Rotimi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Low genetic structure of the Sahel/Savannah belt, revealed by uniparental markers, inspired the notion of a bidirectional migration corridor situated between the Sahara and tropical rainforests (Černý et al, 2007; Černý et al, 2009; Černý et al, 2011). Other studies, however, stress the importance of pastoralism as a barrier of gene flow (Bučková, Černý, & Novelletto, 2013; Kleisner et al, 2019; Nováčková et al, 2020; Shriner & Rotimi, 2018). In fact, a high degree of endogamy can be observed among the Fulani pastoralists even today (Hampshire & Smith, 2001), especially in fully nomadic groups such as Wodaade (sing.…”
Section: Discussionmentioning
confidence: 99%